Thematic Subject Specific Pedagogy to Integrate 21st Century Learning Skills - Fitri Indriani; Syamsiah Zakariyah (The Indonesian Institute of Science and Technology Research, 2022)
The development of technological advances in the era of Industrial Revolution 4.0 has provided new challenges for education. Teachers have expected to package the subject matter into a comprehensive and educational set of learning. Nevertheless, most teachers cannot design thorough academic knowledge, especially in integrating HOTS, ICT, character, and competence of the 21st century. This research aims to produce learning tools in integrative thematic based on 21st-century skills. The research method used is research and development. Data collection techniques included expert validation sheets, teacher assessments, and student responses. Subject-specific pedagogy (SSP) consists of three products: syllabus, lesson plan, and student worksheet. They are eligible based on expert validation tests. The syllabus score is 4.8, the lesson plan is 4.8, and the student worksheet is 4.7. The assessment results are in the good category Students' response to the worksheet from the aspect of content feasibility, presentation aspect, linguistic aspect, and visual aspect entered is in the excellent category. Thus, SSP in 21st-century skills is suitable for elementary school students.